1998
DOI: 10.1128/aac.42.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Possible Correlations between Antifungal Susceptibilities of Filamentous Fungi In Vitro and Antifungal Treatment Outcomes in Animal Infection Models

Abstract: Nine isolates of filamentous fungi previously tested in 11 different laboratories for their susceptibilities to amphotericin B and itraconazole in vitro were injected intravenously into mice and guinea pigs, and responses to treatment with both agents were studied. The experiments were done in a single laboratory. Mean survival times, the percentages of animals surviving 12 days after infection, and culture results for samples of deep organs obtained postmortem were used as markers of antifungal efficacy. Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(53 citation statements)
references
References 23 publications
3
49
0
1
Order By: Relevance
“…Culture-independent detection is needed since Scedosporium strains have reduced susceptibilities to many antifungal agents. Early diagnosis is the key to successful antifungal treatment (8,21,35). At present, no comprehensive data exist on mortality rates attributable to the newly circumscribed Pseudallescheria and Scedosporium species in different patient groups (e.g., transplant recipients or cystic fibrosis pa-tients).…”
Section: Discussionmentioning
confidence: 99%
“…Culture-independent detection is needed since Scedosporium strains have reduced susceptibilities to many antifungal agents. Early diagnosis is the key to successful antifungal treatment (8,21,35). At present, no comprehensive data exist on mortality rates attributable to the newly circumscribed Pseudallescheria and Scedosporium species in different patient groups (e.g., transplant recipients or cystic fibrosis pa-tients).…”
Section: Discussionmentioning
confidence: 99%
“…The response, however, may have been secondary to a recovering neutrophil count [146]. Most in-vitro and animal studies have shown poor efficacy of azoles [51,145,[147][148][149][150]. Azoles were not effective against Rhizopus infection in guinea-pig and murine models [145].…”
Section: Entomophthoramycosismentioning
confidence: 99%
“…It is a matter of concern now that amphotericin B resistance in Aspergillus non-fumigatus strains is increasingly being reported. [7][8][9] In addition emerging triazole resistance in A. fumigatus is worrisome, as resistance is correlated with treatment failure. 10 In the Netherlands, azole resistance in A. fumigatus strains was 2% till 2006, but is expected to rise.…”
Section: Introductionmentioning
confidence: 99%